Response of broilers on the diet containing fermented palm oil sludge stored at various length of time - Bintang, I.A.K; Sinurat, A.P; Purwadaria, T (Indonesian Journal of Animal and Veterinary Sciences, 2003)
An experiment was conducted to study the response of broilers on the diet containing fermented palm oil sludge with Aspergillus niger stored at different length of time. The research was carried out in Research Institute for Animal Production Ciawi, Bogor. The experiment was conducted based on completely randomized design using 245 day old broiler chicks with 5 replicates. They were allotted to 7 diets containing one control without palm oil sludge (R0), 5 and 10% of fresh-fermented palm oil sludge (LSF) (R1 and R2), 5 and 10% of LSF stored at room temperature for 2 months (R3 and R4) and stored for 3 months (R5 and R6). Diets were fed ad libitum for 5 weeks. Feed intake, weight gain, feed conversion ratio, and carcass yields were observed as parameters. Results showed that no parameters were significantly affected by the treatments. It is concluded that 10% of fermented palm oil sludge could be included in diet of broilers even after three months storage at room temperature. Â  Key words: Broiler, fermented palm oil sludge, storage period